2016
DOI: 10.1097/md.0000000000003255
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Kidney Disease is Associated With Upper Tract Urothelial Carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The most important strength of the current study was unlikely to the well-known higher risk of upper tract urothelial carcinoma in the CKD women in the world, including Taiwan, [ 6 , 16 , 20 26 , 69 ] and it might be the first nationwide, population-based study to investigate the risk of GC in the CKD women in Asia. In addition, using this national population-based study, we further confirmed that GC is an age-dependent disease.…”
Section: Discussionmentioning
confidence: 99%
“…The most important strength of the current study was unlikely to the well-known higher risk of upper tract urothelial carcinoma in the CKD women in the world, including Taiwan, [ 6 , 16 , 20 26 , 69 ] and it might be the first nationwide, population-based study to investigate the risk of GC in the CKD women in Asia. In addition, using this national population-based study, we further confirmed that GC is an age-dependent disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low preoperative eGFR ( < 60 mL/min/1.73m 2 ) had worse RFS, CSS, and OS than those with higher eGFR (≥60 mL/min/1.73m 2 ). Despite the fact that the exact mechanisms by which relative renal insufficiency leads to UTUC, and possibly to more aggressive UTUC, are unknown, there is some evidence from a population-based cohort study that demonstrates the association between decreased renal function and risk of urinary tract cancer including UTUC [ 12 - 14 ]. CKD is common in the elderly population and is suggested as an important risk factor for the development of many cancers including those of the prostate and urinary tract [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among 267 patients with urothelial carcinoma, 11%, 55%, and 71% of those with none/mild CKD, CKD stage III, and CKD stage IV/V, respectively, had UTUC. Recently, a more large-scale and long-term follow-up study using a national health database in Taiwan demonstrated that CKD patients have an elevated risk for UTUC [ 14 ]. In the multivariate analysis, CKD patients had a 1.63-fold higher risk of UTUC than the non-CKD group (adjusted HR: 1.63, 95% CI: 1.26-2.13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the articles “Infant stool color card screening helps reduce the hospitalization rate and mortality of biliary atresia: A 14-year nationwide cohort study in Taiwan” [1] and “Chronic kidney disease is associated with upper tract urothelial carcinoma: A nationwide population-based cohort study in Taiwan”, [2] which appeared in Volume 95, Issue 12 and Volume 95, Issue 14, respectively, of Medicine , a university affiliation was originally given incorrectly. Dr. Chen's affiliation in both articles should have read “Department of Pediatrics (SC-CC), School of Medicine, College of Medicine, Taipei Medical University, Taipei City, Taiwan”.…”
mentioning
confidence: 99%